Developing a tax education blueprint for non accounting curriculum in Malaysia - Lai, Ming Ling; Yaacob, Zalilawati; Mahat, Mohd Amran; Choong, Kwai Fatt (2012)
This primary objective of this study is to develop a tax education blueprint for the non-accounting curriculum in Malaysia. A questionnaire survey was conducted 1) to find out the quest for tax education among Malaysian undergraduates from the non accounting disciplines; (ii) to examine the level of tax knowledge among non accounting undergraduates; (iii) to identify the instructional methods to be used, iv) to identify the relevant tax topics to be covered in tax course for the non-accounting curriculum; (v) to solicit tax practitioners and tax academics opinions on introducing tax education into non-accounting curriculum. A self-administered survey was conducted from in the month of February to April 20 II in three public universities in Malaysia. In total, 995 usable responses were received and used for data analysis. The respondents profiles show 67.1% (668) from Universiti Teknologi MARA, 16.5% (164) from Universiti Putra Malaysia and 16.3% (163) from Universiti kebangsaan Malaysia. Ths survey found (I) majority of the respondents were in favour that tax education should be introduced to their faculties and become part of their learning subject (mean score of 3.34, significant at p< 0.001). (ii) Just 10.6% of the respondents exhibited that they had high level of tax knowledge, 44.5% of them possessed medium level of basic tax knowledge and 44.9% had low level of basic tax knowledge. Although SAS has been implemented for 7 years on salaried individuals, the result indicates that the respondents' level of tax knowledge is considered low. (iii) The most preferred methods of teaching tax are using case studies (mean=3.31, significant at p<0.001) and face-to-face classroom learning (mean=3.28, significant at p<0.001). Whilst, the least preferred method of teaching is through e-Iearning (mean =2.86, significant at p<0.001). (iv) the topics that the respondents like to learn the most are personal taxation, tax planning for individual, and basic concepts of taxation with the mean score of 3.59, 3.58 and 3.52 respectively (significant at p<0.001), and (v) Tax practitioners interviewed were in favour of introduce tax education to non-accounting curriculum; however accounting academicians were apprehensive to introduce tax subject to non-accounting curriculum as they were concerned about the availabiltiy of tax lecturers.